2018
DOI: 10.1111/ipd.12452
|View full text |Cite
|
Sign up to set email alerts
|

The family impact of dental general anaesthesia in children: A meta‐analysis

Abstract: Background The health and well‐being of children are intimately linked to their parents’ physical, emotional, and social health and social circumstances. Aim To conduct a meta‐analysis of studies that have used the Early Childhood Oral Health Impact Scale (ECOHIS) and Child Oral Health‐Related Quality of Life (COHRQoL) instruments, to evaluate the family impact scale (FIS) changes following their children's dental treatment under general anaesthesia (DGA). Methodology A systematic search was undertaken using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Although any OHRQoL measure that attempts to assess outcomes for participants who are not yet able to articulate their own opinions has limitations, 24 the differences in both mean scores and the prevalence of impacts across the FIS scale and subscales suggest that the intervention was beneficial. The differences observed were similar to the medium‐to‐large effect sizes reported in another nine studies that used the FIS to assess changes in OHRQoL after dental treatment under general anaesthesia 25 …”
Section: Discussionsupporting
confidence: 85%
“…Although any OHRQoL measure that attempts to assess outcomes for participants who are not yet able to articulate their own opinions has limitations, 24 the differences in both mean scores and the prevalence of impacts across the FIS scale and subscales suggest that the intervention was beneficial. The differences observed were similar to the medium‐to‐large effect sizes reported in another nine studies that used the FIS to assess changes in OHRQoL after dental treatment under general anaesthesia 25 …”
Section: Discussionsupporting
confidence: 85%
“…48 There is evidence to support an improvement in OHRQoL following comprehensive dental rehabilitation under general anaesthesia. 49,50 To date, there are no published studies that comprehensively assess dental patient-reported outcomes (dPRO) after the use of alternative pulp medicaments in primary teeth. 48 However, from the available published studies, the absence of soft tissue pathology and pain is used as a measure of clinical success.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…People with SHCN, including those with intellectual disability (ID), often show poor oral health due to various developmental disorders and/or cognitive disabilities, along with limitations to tolerate routine treatment at the dental clinic ( 1 ). In addition, general anesthesia (GA) is required in many of them to provide safe dental treatment given their persistent inability to cooperate, the severity of their dental problems, and the complex and extensive procedures they often need ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%